MMSE receivers for non-linearly distorted OFDM signals - J. M. B. Oliveira (2009)
In this paper, we have derived the structure of the minimum mean-squared error (MMSE) receiver for non-linearly distorted orthogonal frequency division multiplexer (OFDM) signals in additive white Gaussian noise (AWGN). We demonstrate that this receiver consists of a set of correlators or a set of filters matched to every possible frequency components in the non-linearly distorted OFDM signal followed by a simple linear transformation. Simulation results show that the MMSE receiver outperforms the conventional one, particularly in the presence of strong nonlinearities. Finally, we conjecture that this receiver is useful in OFDM based fiber-radio applications.